Bahasa Inggris - Ria Astuti; Erni Munastiwi; Muqowim; Muammar Qadafi (State Islamic Institute of Madura, 2022)
Early use of technology always has advantages and disadvantages in social interactions. Some neighborhood organizations believe that technology may promote accountability, pragmatism, security, and convenience. Other groups, meanwhile, believe that gadgets are prone to criminality. Gadgets must be present since they are an unavoidable aspect of life. Use intended for young children requires parental supervision. Similarly, technology can be employed as a teaching tool. The study's goal was to investigate how Islamic education ideals are taught to young children through the use of technology. This study used descriptive qualitative research as its methodology. ways for gathering data through observation, interviews, and documentation. Ten parents of young children participated as informants in the study. Data reduction and exposure stages, as well as inference and data verification, are all used in technical analysis of the data. By using three different procedures and data sources, the veracity of the data is tested. The study's findings demonstrate that: First, early childhood care can be provided using either an authoritative parenting style, which limits children's independence while granting them authority, or a permissive parenting style, which pampers them. Second, using technology as media is one way that parents today are instilling Islamic education values which includes aspects of aqidah, worship (ibadah), and morals (akhlak) in their children. Third, gadgets have a negative impact on early childhood including cyberbullying, pornography, blasphemy and speaking impolitely in cyberspace, then children think instantly, are less active, addicted to gadgets and result in a consumptive lifestyle.